Parameters Optimization of PID Controller for an Artillery Coordinator Based on Multi-Objective Genetic Algorithm - Chen, Junhua; Chen, Longmiao; Miao, Wei; Chen, Guangsong (International Conference on Industrial Mechatronics and Automation (Online), 2020)
The Artillery coordinator is vital important to the accuracy of artillery firing. However, state-of-the-art optimization methods to the control parameters of artillery coordinator, always utilize single subject modeling and analysis, which result in the coupling effects between different disciplines are not considered, In this paper, we propose a multi-objective optimization analysis method to decrease the mechanical vibration of the artillery coordinator and improve its control performance. Specifically, we take the mechanical structure, control parameters and hydraulic characteristics of the artillery coordinator into consideration and formulate the mathematical multidisciplinary model of the artillery. For this model, we target on the PID controller's variables optimization, and adopt the genetic algorithm to realize the multi-objective optimization analysis. Finally, three examples are adopted to verify the effectiveness of the optimization results. Simulation results show that the proposed multi-objective model is efficient and feasible.